PERKEMBANGAN EFISIENSI DAN EFEKTIFITAS PEMUNGUTAN PAJAK DAERAH SEBAGAI SUMBER PENDAPATAN ASLI DAERAH DI KOTA SURAKARTA PERI ODE TAHUN 1993-2003 - Magdalena Nany; Endang Satyawati (Badan Perencanaan Pembangunan, Penelitian dan Pengembangan Daerah Provinsi Jawa Tengah, 2004)
The objective of this research was to identify the development of the efficiency oflocal tax collection in Surakarta city. This research was also intended to identify the development of the effectiveness of local tax colJection in Surakarta city. Annual local tax data during I 993 - 2003 were analyzed by trend analysis using least square method. The results show that the efficiency of local tax collection in Surakarta city during I 993-2003 tend to decline. The results also show that the effectiveness of local tax collection in Surakarta city during 1993- 2003 tend to decline.